2013
DOI: 10.1007/s00520-013-1999-9
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analysis of phase III clinical studies of palonosetron versus ondansetron, dolasetron, and granisetron in the prevention of chemotherapy-induced nausea and vomiting (CINV)

Abstract: PurposePreventing chemotherapy-induced nausea and vomiting (CINV) is integral to treatment success in patients with cancer. This analysis was undertaken to assess the relative efficacy and safety of palonosetron versus older 5HT3 RAs in preventing CINV associated with moderately or highly emetogenic chemotherapy.MethodsPatient-level data from four randomized, double-blind, phase III trials comparing palonosetron 0.25 or 0.75 mg with ondansetron 32 mg, dolasetron 100 mg, or granisetron 40 μg/kg were analyzed. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…28 The CINV drugs are known to mediate their effects by acting on this region in the brain and brain stem. 1,29 Further confirmation of this brain region will have to be carried out.…”
mentioning
confidence: 99%
“…28 The CINV drugs are known to mediate their effects by acting on this region in the brain and brain stem. 1,29 Further confirmation of this brain region will have to be carried out.…”
mentioning
confidence: 99%
“…Several investigators reported that palonosetron provides more effective CINV control through the entire chemotherapy process (including the delayed phase) than any other 5-HT3 receptor to date (16,17). The present results similarly observed that palonosetron is effective for controlling acute-and delayed-phase nausea through the entire treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…concluded that palonosetron was more effective than the first-generation receptor antagonists in preventing acute and delayed CINV in patients receiving MEC or HEC, regardless of the use of concomitant corticosteroids. Schwartzberg et al [47] concluded that palonosetron is more effective than the first-generation 5-HT 3 receptor antagonists in controlling CINV in the delayed and overall post-chemotherapy periods based on a pooled analysis of Phase III clinical studies of palonosetron versus ondansetron, dolasetron, and granisetron. In an additional review, Popovic et al [48] concluded that palonosetron is safer and more efficacious than the other 5-HT 3 receptor antagonists.…”
Section: Clinical Efficacy Of Palonosetron In Single-day Chemotherapymentioning
confidence: 98%
“…The adverse reactions reported were the most common reactions reported for the 5-HT 3 receptor antagonist class, headache, and constipation. All other reactions occurred at an incidence of £ 1% in patients treated with 0.25 mg of palonosetron [44][45][46][47][48][49][50].…”
Section: Safety and Tolerability Of Palonosetronmentioning
confidence: 99%